Mazagaon Koliwada road signage - Mumbai Archive Project Team (Jio Institute, 2024)
Adjoining the docks, Mazagaon Koliwada is among the oldest Koli settlements in Mumbai, though nothing much of the historical village has survived in modern times. It is home to diverse communities, including Parsis, Muslims, East Indian Catholics, Jews, and others, who have lived here for generations. Mazagaon is dotted with architectural landmarks and heritage buildings, which reflect its cosmopolitan social fabric.